DESAIN LinEq-TV MAZE UNTUK MEMFASILITASI RETENSI DAN MINAT BELAJAR PESERTA DIDIK - iwan, Ridwan Akbar Nur Alam; Elvandari, Teti Hotimah; Wahid, Abdul (Universitas Islam Nusantara, 2024)
What happens in the field is that students lack interest in learning mathematics because mathematics is considered a difficult subject to understand and has an impact on students' memory of the material that has been taught. This is a challenge for educators to find the right learning method. So, it is necessary to develop a learning method with the help of games for SPLDV material. The purpose of this study was to determine the feasibility, retention, and interest in learning after learning mathematics with the help of math maze on SPLDV material. The research method used is Design Research (DR). with ADDIE design. Data were obtained through media expert validators and material experts, as well as students. Data collection techniques include media and material expert validation sheets, post tests and retests, learning interest questionnaires, and interviews. The results of the validation of math maze-based learning media include very valid criteria. Retention of student learning outcomes after learning SPLDV through math maze is classified in the high category. Students' interest in learning after learning SPLDV through math maze is classified in the very interested category.